2018
DOI: 10.1017/s0022029918000286
|View full text |Cite
|
Sign up to set email alerts
|

Effect of season and breed on physiological and blood parameters in buffaloes

Abstract: In this Research Communication we describe the effect of temperature and humidity index (THI) on various physiological traits, the plasma heat shock protein 70 (HSP70), heat shock protein 90 (HSP90) and cortisol levels and other blood parameters in crossbred buffalo (Nili-Ravi × Murrah) and Mediterranean buffalo to compare their tolerance to heat stress. As expected, crossbred buffalo had a significantly higher rectal temperature (RT), body surface temperature (BT), respiratory rate (RR), HSP70 and HSP90 level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 17 publications
4
22
0
Order By: Relevance
“…Elevated temperature increased the plasma HSP90 and HSP70 levels more markedly in HT than in NHT individuals, coinciding to previous study in cattle [33] and rodents [34]. Higher plasma cortisol levels observed in the HT than in NHT individuals after the heat stress challenge in the present study is consistent with those reported by Hammond, et al [35] in heat tolerant Romosinuano (RO) and heat-sensitive Angus (ANG) heifers after heat stress, and Shenhe et al [16] in Mediterranean and Crossbred buffalo after heat stress. Thus, our findings showed that the selection of HT and NHT Chinese Holstein dairy cows is practical and can be used as reference for further analysis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Elevated temperature increased the plasma HSP90 and HSP70 levels more markedly in HT than in NHT individuals, coinciding to previous study in cattle [33] and rodents [34]. Higher plasma cortisol levels observed in the HT than in NHT individuals after the heat stress challenge in the present study is consistent with those reported by Hammond, et al [35] in heat tolerant Romosinuano (RO) and heat-sensitive Angus (ANG) heifers after heat stress, and Shenhe et al [16] in Mediterranean and Crossbred buffalo after heat stress. Thus, our findings showed that the selection of HT and NHT Chinese Holstein dairy cows is practical and can be used as reference for further analysis.…”
Section: Discussionsupporting
confidence: 93%
“…Heat stress indexes including physiological indicators and milk yield change were used to investigate the response of Chinese Holstein dairy cows (n = 42) to heat stress. First, rectal temperature (RT) and respiratory rate (RR) were detected and recorded at 1:00-3:00 pm for 7 consecutive days in June and August for each experimental cow according to previous methods [16]. Milk yield was recorded three times per day for 7 consecutive days at the beginning of June and August, respectively, and changes in milk yield per cow owing to heat stress was calculated as the difference in the milk yield between two months.…”
Section: Experiments Design and Sample Collectionmentioning
confidence: 99%
“…Similar findings regarding high cortisol contents in summer have been reported earlier in Egyptian buffaloes ( 1 ), Murrah buffaloes ( 17 , 29 ), and Sahiwal cows ( 13 ). Moreover, elevated cortisol levels have been observed in crossbred buffaloes (Nili-Ravi × Murrah) as compared to purebred Mediterranean buffaloes ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, they still feel great distress if exposed to direct solar radiation or working in the sunlight during hot weather, thereby affecting their production performance. For example, increased rectal temperature (RT) and respiratory rate (RR) result in a reduction of milk production and poor fertility in buffaloes (Vale, 2010; Maf, 2017; Shenhe et al, 2018). Three mitigation strategies can be recently used for combating the adverse effects of summer heat stress in animals, such as physical modification of the environment (Fournel et al, 2017), development of genetically heat tolerant breeds (Breede and Collier, 1986), and nutritional modification (West, 1999).…”
Section: Introductionmentioning
confidence: 99%